MECHANICAL PROPERTIES OF 3D PRINTED AND MILLED SPACE MAINTAINERS USED IN PREVENTIVE ORTHODONTICS - Bianca Dragoș; Dana-Cristina Bratu; George Popa; Magda-Mihaela Luca; Remus-Christian Bratu; Cosmin Sinescu (Romanian Journal of Oral Rehabilitation)
Aim of the study: This study aimed to evaluate the mechanical strength, when subjected to compressive forces, of aesthetic space maintainers manufactured through various digitally-assisted methods specifically, additive techniques (LCD and SLA) and subtractive milling. Materials and methods: Space maintainer designs were digitally modelled in Exocad and then produced by LCD printing using TC100 resin and plant-based Anycubic resin, by stereolithography (SLA) printing using Next Dent and Harz Labs resins, and by a subtractive technique using Tempo Block PMMA milling discs (Sid Dental). All samples underwent compression testing using the Zwick/Roell Z 005 machine. Results: A one-way ANOVA statistical test revealed significant differences in the compression breaking force among the four groups with milled samples showing a significantly higher strength than all 3D printed samples (LCD, SLA_Harz, and SLA_Next). Tukey post hoc tests confirmed these differences (p < 0.001), while no significant differences were found among the 3D printed groups. The soy-based Anycubic resin samples exhibited high elasticity, leading to deformation without fracture, and were excluded from the study due to their inability to properly maintain the mesiodistal space. Conclusions: Beyond the aesthetic benefit, the milled space maintainers proved to offer a substantial advantage in terms of mechanical strength over those fabricated with additive printing techniques (LCD and SLA), making the subtractive manufacturing technique more suitable for clinical applications that involve higher mechanical stress.